Australian bat lyssavirus: implications for public health. Issue 11 (15th December 2014) - Francis, Joshua R; McCall, Bradley J; Hutchinson, Penny; Powell, Jodie; Vaska, Vikram L; Nourse, Clare
Summary: Australian bat lyssavirus (ABLV) infection in humans is rare but fatal, with no proven effective therapy. ABLV infection can be prevented by administration of a post‐exposure prophylaxis regimen of human rabies immunoglobulin and rabies vaccine. All Australian bats (flying foxes and microbats) should be considered to be carrying ABLV unless proven otherwise. Any bat‐related injury (bite, scratch or mucosal exposure to bat saliva or neural tissue) should be notified immediately to the relevant public health unit — no matter how small the injury or how long ago it occurred. Human‐to‐human transmission of ABLV has not been reported but is theoretically possible. Standard infection control precautions should be employed when managing patients with suspected or confirmed ABLV infection.